Acceptance of the German e-mental health portal www.psychenet.de: an online survey - Tlach, Lisa; Thiel, Juliane; Härter, Martin; Liebherz, Sarah; Dirmaier, Jörg (PeerJ Preprints, 2016)
Background. Taking into account the high prevalence of mental disorders and the multiple barriers to the use of mental health services, new forms of fostering patient information, involvement, and self-management are needed to complement existing mental health services. The study aimed at investigating acceptance regarding design and content of the e-mental health portal www.psychenet.de. Methods. An online cross-sectional survey was conducted between May 2013 and May 2015 using a self-administered questionnaire including items on perceived ease of use, perceived usefulness, attitude towards using, and perceived trust. Effects of different participants’ characteristics on the portals’ acceptance were analyzed. Results. The majority of the N=252 respondents suffered from mental disorders (n=139) or were relatives from persons with mental disorders (n=65). The portal was assessed as “good” or “very good” by 71% of the respondents. High levels of agreement (89-96%) were shown for statements on the perceived ease of use, the behavioral intention to use the portal, and the trustworthiness of the portal. Lower levels of agreement were shown for some statements on the perceived usefulness of the portals’ content. There were no effects of different participants’ characteristics on the perceived ease of use, the perceived usefulness, the attitude towards using the website and the perceived trust. Discussion. This survey provides preliminary evidence that the e-mental health portal www.psychenet.de appears to be a usable, useful and trustworthy information resource for a broad target group. The behavioral usefulness of the portals’ content might be improved by integrating more activating patient decision aids.
Keywords: health information; process evaluation; internet; mental health